ANALISIS PERSEPSI PENGGUNA LAPORAN KEUANGAN PADA MASYARAKAT - Hesti Ning Tyas; Hwihanus, Hwihanus (Cahaya Ilmu Bangsa, 2024)
This study aims to analyze the perception of financial report users among the public using qualitative research methods. Financial reports play an important role as an information tool for various stakeholders, including the general public, in understanding the financial condition of an entity. However, the level of public understanding of financial reports often varies. In this study, data were collected through an in-depth questionnaire with several respondents selectedpurposively, with different backgrounds related to knowledge and use of financial reports. Data analysis was carried out using a descriptive approach, which aims to identify patterns of public understanding, interpretation, and trust in financial reports. The results of this study indicate that public perception of financial reports is influenced by education level, experience, and access to financial information. These findings are expected to provide insight into thedevelopment of more effective financial education strategies, as well as encourage transparency of financialinformation among the wider community.